Animated Video Development in Thematic Learning in the Fifth Grade of Elementary School - Faujiah, Erika; Nulhakim, Lukman; Hendracipta, Nana (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Thematic learning for elementary students is challenging since combining many subjects matter in one topic so the appropriate medium to deliver the subject should be taken into consideration. This study aims to develop animated videos in fifth grade at SDN Cijeruk and determine the video’s feasibility and student responses after using the video. The background of this research is that the teacher only used the lecture method and textbooks, making students feel bored and sleepy. In addition, teachers did not make good use of school facilities with laptops, InFocus, and speakers to apply digital learning media. Teachers also did not make use of their soft skills in using technology. This research method was RD (Research and Development) using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The results of the material expert validation from the two validators obtained an average percentage of 89.5%, on the criteria of "very feasible." The validation of linguists from the two validators attained an average percentage of 87% on the "very feasible" criterion. Furthermore, the average percentage of media expert validation from the two validators was 88.5% in the "very feasible" criteria. Hence, the overall average percentage of the material, language, and media validators was 88.3% in the "very feasible" criteria. For student responses, an average percentage of 97.475% was also obtained in the "very good" criteria. Based on the validation results and student responses, this animated video is feasible for school use.